Evaluation of the replication, pathogenicity, and immunogenicity of avian paramyxovirus (APMV) serotypes 2, 3, 4, 5, 7, and 9 in rhesus macaques. - Sunil K Khattar; Baibaswata Nayak; Shin-Hee Kim; Sa Xiao; Sweety Samal; Anandan Paldurai; Ursula J Buchholz; Peter L Collins; Siba K Samal (PLoS ONE, 2013)
Avian paramyxoviruses (APMV) serotypes 1-9 are frequently isolated from domestic and wild birds worldwide. APMV-1 (also called Newcastle disease virus, NDV) is attenuated in non-human primates and is being developed as a candidate human vaccine vector. The vector potential of the other serotypes was unknown. In the present study, we evaluated nine different biologically- or recombinantly-derived APMV strains for the ability to replicate and cause disease in rhesus macaque model. Five of the viruses were: biologically-derived wild type (wt) APMV-2, -3, -5, -7 and -9. Another virus was a recombinant (r) version of wt APMV-4. The remaining three viruses were versions of wt rAPMV-2, -4 and -7 in which the F cleavage site had been modified to be multi-basic. Rhesus macaques were inoculated intranasally and intratracheally and monitored for clinical disease, virus shedding from the upper and lower respiratory tract, and seroconversion. Virus shedding was not detected for wt APMV-5. Very limited shedding was detected for wt rAPMV-4 and modified rAPMV-4, and only in a subset of animals. Shedding by the other viruses was detected in every infected animal, and usually from both the upper and lower respiratory tract. In particular, shedding over a number of days in every animal was observed for modified rAPMV-2, wt APMV-7, and modified rAPMV-7. Modification of the F protein cleavage site appeared to increase shedding by wt rAPMV-2 and marginally by wt rAPMV-4. All APMVs except wt APMV-5 induced a virus-specific serum antibody response in all infected animals. None of the animals exhibited any clinical disease signs. These results indicate that APMVs 2, 3, 4, 7, and 9 are competent to infect non-human primates, but are moderately-to-highly restricted, depending on the serotype. This suggests that they are not likely to significantly infect primates in nature, and represent promising attenuated candidates for vector development.